The quality of oncology nursing care: A cross sectional survey in three countries in Europe - Charalambous, Andreas; Adamakidou, Theodoula; Cloconi, Constantina; Charalambous, Melanie; Tsitsi, Theologia; Vondráčková, Lucie; Bužgová, Radka (My University, 2017)
Purpose The increase in patients diagnosed with and living with cancer calls for the provision of quality nursing care within this paradigm, one that can reflect the complex needs of the patient that cancer and its treatments induce. The study aimed to evaluate the quality of oncology nursing care, as perceived, by hospitalized cancer patients in three European countries. Methods This was a cross-sectional descriptive study. In-patients diagnosed with cancer were selected based on explicit inclusion and exclusion criteria. Data was collected with the Quality of Oncology Nursing Care Scale- QONCS, comprising of 34 items grouped in 5 domains. Sociodemographic data was also retrieved. Results The sample included 610 patients receiving care in 2 hospitals in Cyprus (n = 274), 1 hospital in Greece (n = 144) and 2 hospitals in the Czech Republic (n = 192). Statistically significant differences were found between the three countries and across all domains of the QONCS, with the exception of the spiritual and religious care (p = 0.136). Age and days of treatment produced statistically significant differences across all the domains of the QONCS, whilst gender did not produced any statistically significant differences (p ranged from (0.136–0.369). Conclusion This is one of the first studies that provide evidence on the Quality of Nursing Care delivered to patients diagnosed with cancer in various European countries. Discrepancies were found between the participating countries. However, the provision of spiritual and religious care by the nurses received the lowest scores across the three participating countries.
Keywords: Cancer patients; Cross-country comparison; Hospitalised patients; Nursing care; Quality